A QoS MAC Protocol for Prioritized Data in Energy Harvesting Wireless Sensor Networks - SOHAIL, SOHAIL (2018)
Wireless sensor networks (WSNs) consist of multiple sensor nodes that have the ability to sense, measure and gather information from the surrounding environment. The battery-powered wireless sensor networks (BP-WSNs) have limited lifespan. Therefore, their network performance is always a tradeoff for lifetime. Recently, energy harvesting technology has made it possible to replenish energy by using external energy sources in energy harvesting wireless sensor networks (EH-WSNs). Therefore, it addresses the energy issue faced by BP-WSNs and can also improve the network performance.